Middlemen’s Perceptions of Relationship Marketing Toward Main Suppliers and Main Customers in Tasikmalaya Regency - Rudhiana Salam; Metty Agustine Primary; Rahmat Rahmat (Asosiasi Dosen Muda Indonesia, 2025)
This study aims to analyze coconut sugar middlemen’s perceptions of their primary suppliers and key customers in Tonjongsari Village, Cikalong District, Tasikmalaya Regency, based on four dimensions of relationship marketing: trust, satisfaction, commitment, and communication. A descriptive quantitative approach was used, and the Wilcoxon Signed Ranks Test was employed to assess perception differences across each dimension among 12 active middlemen. The results show no significant differences in the dimensions of trust (Z = -1.732; p = 0.083), commitment (Z = 0.000; p = 1.000), and satisfaction (Z = -1.414; p = 0.157). However, the communication dimension showed a near-significant value (Z = -1.890; p = 0.059), indicating a potential imbalance in perceptions. The fact that most business relationships have lasted more than 10 years and transaction volumes remain relatively stable suggests that long-term relationships have been established and play a vital role in maintaining the stability of coconut sugar distribution. This study highlights the importance of strengthening communication as a strategy to enhance the effectiveness of relationship marketing in the local coconut sugar supply chain.